2021
DOI: 10.1155/2021/5551325
|View full text |Cite|
|
Sign up to set email alerts
|

Target Characteristics and Voltage Mapping of the Matrix in Idiopathic Premature Ventricular Contractions Originating from the Right Ventricular Outflow Tract

Abstract: Background. The study was aimed at exploring the electrophysiological characteristics (EPS) of the optimal ablation site and its relationship with electroanatomic voltage mapping (EVM) in idiopathic premature ventricular contractions (PVCs) originating from the right ventricular outflow tract (RVOT). Methods. A total of 28 patients with idiopathic RVOT PVCs underwent successful ablation and EVM using a 3D electroanatomical mapping (CARTO) system. Results. Both bipolar and unipolar EVM showed a similar band-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%